Examine the Effect of Various Health Problems Due To Practice of Child Marriage: Exploring the Impact of Child Marriage on Health and Human Rights (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Youth marriage is considered a common clinical problem around the world and is widely reflected in various legitimate tools. The Universal Declaration of Human Rights states that people must marry directly by mutual consent and must be of age. Marriage of young adults hinders the achievement of the Millennium Development Goals, especially goals one to five eliminate nervousness, empower leaders, empower women, reduce juvenile mortality, and improve maternal development. You have two or three rights guaranteed by the Convention on the Rights of the Child, including the benefits of education, freedom from a variety of physical or mental crimes, injury or ill-treatment, including sexual abuse, and a variety of sexual abuse. Ensure a wide range of abuses that affect part of the aid provided by the child's organization and specifically, as in this document, for the benefit of the most accessible care expectation.